Textology of Shakarim Kudaiberdiuly’s рoem «Boyawly Suyr» - Shayakhimov Д.Қ.; Tangsykbay Ә.Қ.; Kenzhalin Қ.К.; Aubakirova Б.К. (Turkic Studies Journal, 2026)
The article presents a comparative analysis of the printed editions and manuscript sources of Shakarim Kudaiberdiuly’s poem ‘Boyauly Suyr’ (‘The Painted Marmot’), which was published at different times. Since the poet’s works were edited using different editorial approaches, textual consistency has not been maintained, resulting in discrepancies at the lexical, morphological, and syntactic levels. These discrepancies complicate precise scholarly interpretations of the poem’s poetic structure and semantic content. Therefore, systematically comparing available sources and identifying their variant readings is an important objective of contemporary Kazakh textual scholarship. Due to the existence of multiple manuscript versions of the poem and the absence of textological analysis, the present research focuses on Boyauly Suyr. Given the existence of multiple manuscript versions and the absence of comprehensive textological study, this research focuses specifically on ‘Boyauly Suyr’. The study employs comparative, descriptive, and analytical methods to examine differences between the textual versions. The primary source is the facsimile edition of the collection ‘Qazaq Aynasy’ (‘The Mirror of the Kazakhs’), published in Semey in 1912 by the Yardam Press, along with its later Cyrillic transcription. Several editions published between 1988 and 2018 are also included in the comparative corpus. The scholarly contribution of the study lies in introducing a previously unexamined, folkloric version of the poem, recorded in 1972 by poet K. Altynbaev, and a manuscript version, documented in the early 20th century by singer A. Aldazharuly and later presented by Sh. Korpebay, into academic circulation. Both versions are treated as independent textual witnesses within the comparative framework. The analysis reveals numerous textual variations. Some of these variations can be attributed to transcriptional shifts occurring during the transition from Arabic script to modern Kazakh Cyrillic (e.g., "azar" to "äzer", "beyshara" to "bishara", "dybys" to "dabys", "shyny" to "shyn", "äbden" to "äbdän" and "nagyp" to "negyp"). Other lexical substitutions (e.g., «asyl» – “zhasyl”, “zholğa tüsip” – “orğa tüsip”, “qubylyp” – “qulpyryp” and “tañqalady” – “añdanady” etc.) significantly affect the poem’s imagery and semantic nuances. A comparison of the versions recorded by K. Altynbaev and Sh. Korpebay with the presumed original suggests that the former underwent more extensive adaptation, possibly reflecting the text’s folkloric transmission. In contrast, the latter version remains closer to the original and may be associated with the performance tradition of A. Aldazharuly, whose repertoire was reportedly supervised by Shakarim. Overall, the findings demonstrate that textual scholarship on Shakarim’s poetry remains an open field for further research, as even a short poem exhibits substantial variability across its extant versions.